CHANGING PERSONAL CARE AND HEALTHCARE BEHAVIOR BY PHYSICIANS DURING THE COVID-19 PANDEMIC: EVIDENCE FROM KAZAKHSTAN - Bazarkulova, Dana (Nazarbayev University School of Sciences and Humanities, 2021)
The COVID-19 pandemic and the resulting economic shutdowns have created increased stress for men and women worldwide. Those who work in healthcare may be more susceptible to increased stress and anxiety which, left unchecked, could have both short- and long-term effects on the workers themselves, their patients, and the healthcare system.
Keywords: COVID-19; pandemics; personal care; healthcare